A Literature Review on the Role of Mathematics in Enhancing Cyber Security Through Data Encryption - Laily Shodiq , Nur; Hawari, Ammar; Putri, Nabilla Andini; Nurul Faizah, Maira; Wahyunengsih (KH. A. Wahab Hasbullah University, 2025)
This article discusses the important role of mathematics in enhancing cyber security in the data encryption process. The research problem investigates the benefits of applying mathematical principles in maintaining data security amid increasingly complex cyber threats. The study focuses on four main criteria: protecting sensitive information, verifying user identity, preventing intrusions, and protecting network integrity. Mathematical algorithms, binary numbers, and boolean algebra are essential in effectively encrypting data. They not only protect sensitive information from unauthorized access but also verify user authenticity, preventing identity theft and unauthorized system access. By utilizing mathematical theories and algorithms, binary numbers, and boolean algebra, cyber security systems can guarantee data confidentiality, integrity, and availability. In conclusion, the integration of mathematics in cyber security systems is essential to mitigate risks and protect critical digital assets from increasingly sophisticated cyber threats.